2017
DOI: 10.1111/epi.13866
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery of “low grade epilepsy associated neuroepithelial tumors”: A retrospective nationwide Italian study

Abstract: Our nationwide LEATs study gives important insights on factors predicting seizure outcome in refractory epilepsy and determining variability in FCD detection. Timely surgery, regardless of pharmacoresistance and oriented to optimize epileptologic, neuropsychological, and oncologic outcomes should be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 39 publications
7
50
1
1
Order By: Relevance
“…The study included 107 children and is one of the largest series to date in this population. 6,9,12 Our Engel class I outcome of 84% was consistent with previously published studies. 3,5,8,13,18 Interestingly, Englot et al found a similar rate of Engel class I in the largest systematic literature review of seizure outcomes after resection of neuronal-glial tumors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study included 107 children and is one of the largest series to date in this population. 6,9,12 Our Engel class I outcome of 84% was consistent with previously published studies. 3,5,8,13,18 Interestingly, Englot et al found a similar rate of Engel class I in the largest systematic literature review of seizure outcomes after resection of neuronal-glial tumors.…”
Section: Discussionsupporting
confidence: 90%
“…1,2 Last, data exist to support the idea that oncological follow-up and treatment is essential for these tumors. 9 A small percentage of these neuronal-glial tumors can become malignant. One study reports that some tumors recurred as malignancies.…”
mentioning
confidence: 99%
“…15,43,45,47,48,50,52,54,55,66) In an Italian nationwide study of epilepsy surgery for LEATs that included a total of 282 adults and children, older age at surgery was the most significant predictor of persistent seizures, with a 4% increase in the probability of an unfavorable outcome for every year waited. 16) Since previous studies de monstrated no significant difference in surgical outcome between pediatric and adult patients with LEATs, 16,56) the reason for the poor prognosis associated with older age at surgery may be the duration of epilepsy rather than the patient's age itself.…”
Section: Age At Surgerymentioning
confidence: 99%
“…The discordance among previous studies also raises an important question regarding the use of additional corticectomy or additional amygdalohippocampectomy for temporal lobe tumors. 14,16,23,56,60,[67][68][69] Extended resections are mainly performed for temporal tumors, while there is a lack of reports detailing outcomes for extratemporal tumors. 43,67,[69][70][71] One indicator that endorses the application of extended tailored resection is the presence of adjacent dual pathology, such as focal cortical dysplasia or hippocampal sclerosis, that can cause seizures after lesionectomy.…”
Section: Extent Of Resectionmentioning
confidence: 99%
See 1 more Smart Citation